REASON AS A SOURCE OF ISLAMIC LAW: Epistemological Approach - A’yun Sufyan, Qurrotul; Mohammad Sugi Hartono (Islamuna: Jurnal Studi Islam, 2023)
ABSTRACT The existence of reason in humans is a privilege given by Allah SWT. Humans with their intellect can think, do reasoning, and appreciate all of Allah’s creations. Qurâ€™an as a source of basic material in Islamic law provides a large portion of the use of human reason. The method used in this research was library research. The background to the recognition of the role of reason is the fact that the development of social life is followed by various life problems whose answers cannot be found in translation in the Qurâ€™an or Hadith. The results of this study indicate that, first, reason is the power of thought which when used can lead a person to understand the problem he is thinking about. Second, reason functions as a tool for thinking, contemplating, experiencing, and developing intelligent concepts and ideas, very closely related to education. Therefore, reason in its implication towards the goals of Islamic education greatly determines the success or failure of a person in achieving the goals of Islamic education. ABSTRAK Keberadaan akal pada manusia merupakan keistimewaan yang diberikan Allah swt. Manusia dengan akal yang dimilikinya dapat berpikir, melakukan penalaran, dan penghayatan terhadap segala ciptaan Allah swt. Al-Qurâ€™an sebagai sumber materi pokok dalam hukum Islam memberikan porsi yang besar terhadap penggunaan akal pikiran manusia. Metode yang digunakan dalam penelitian ini adalah studi kepustakaan. Latar belakang dari diakuinya peranan akal ini merupakan kenyataan berkembangnya kehidupan masyarakat yang diikuti oleh berbagai permasalahan hidup yang tidak ditemui jawabannya secara harfiah dalam Al-Qurâ€™an maupun Al-Hadits. Hasil penelitian ini menunjukkan bahwa, pertama, akal adalah daya pikir yang bila digunakan dapat mengantarkan seseorang untuk memahami dan memahami masalah yang sedang dipikirkannya. Kedua, akal berfungsi sebagai alat berpikir, merenung dan mengalami serta mengembangkan konsep dan gagasan yang cemerlang, sangat erat hubungannya dengan pendidikan. Maka akal dalam implikasinya terhadap tujuan pendidikan Islam sangat menentukan berhasil atau tidaknya seseorang dalam mencapai tujuan pendidikan Islam.